Optimization of microwave-convective drying of Red Pitaya (Hylocereus Undatus)slices using response surface method - Mariam Firdhaus Mad Nordin (Faculty of Agro Industry and Natural Resources, Universiti Malaysia Kelantan, 2010)
A laboratory scale microwave-convective dryer was designed and built to determine the effects of drying kinetics and quality attributes of red pitaya (Hylocereus) slices. The drying conditions were optimized using the response surface method to arrange the combinations of three process parameters : microwave power density, thickness of red pitaya slices and the drying temperature of the product. The statistical analysis performed on the collected data revealed that the optimum conditions to dry red slices was at temperature of 55'C with an initial microwave power density of 1 W g-1 and a slice thickness of 7.5 mm. It took about 964 minutes to reduce the moisture content to about 10%(db). Slices dried under optimum conditions were then compared to slices of same thickness dried under hot air alone at the same temperature and it took about 2050 minutes to dry the slices to the same final moisture content